2014
DOI: 10.4238/2014.march.17.7
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing implicates PTCH1 and COL17A1 genes in ossification of the posterior longitudinal ligament of the cervical spine in Chinese patients

Abstract: ABSTRACT. Ossification of the posterior longitudinal ligament (OPLL) of the cervical spine is a complex multifactorial disease. Patients with OPLL commonly present with symptoms in their 40s or 50s. The genetic basis of OPLL remains poorly understood. Exome capture combined with massively parallel DNA sequencing has been proposed as an efficient strategy to search for disease-causing genes of both monogenic and multigenic disorders. To identify candidate pathogenic genes associated with OPLL, we performed whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Recent study showed that the incidence rate of OPLL has reach more than 5% in some of the Asian regions outside Japan 21 . The disease also increases with age, with the average onset age of around 50 years old, and the male to female ratio at 2:1 22 . Despite advances in surgery and radiographic technologies, treating OPLL is still a task that has not been improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study showed that the incidence rate of OPLL has reach more than 5% in some of the Asian regions outside Japan 21 . The disease also increases with age, with the average onset age of around 50 years old, and the male to female ratio at 2:1 22 . Despite advances in surgery and radiographic technologies, treating OPLL is still a task that has not been improved.…”
Section: Discussionmentioning
confidence: 99%
“…Beside non-genetic factors like mechanical stress, nutrition, glucose intolerance, and high body mass index, recent studies showed numerous genes are associated with the disease. Most of these genes are vital to the ossification process like NPPS, COL11A2, COL6A1, BMP2, BMP4, TGF-β1, TGF-β3 4 5 6 7 22 24 , and often aberrant expression of these genes can cause the pathological heterogeneous ossification 25 26 . This means a certain disorder in the upstream regulatory network of these critical factors may exists during the pathological process of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations and/or aberrant expressions of collagen genes may induce various pathological phenotypes in connective tissues. Many collagen genes are shown to be associated with OPLL, including COL11A2 ,[ 31 - 34 ] COL6A1 [ 20 , 35 - 37 ] and collagen 17A1 ( COL17A1 ) [ 38 ]. COL11A2 is the type XI collagen that associates with type II collagen, the main collagenous component of cartilage.…”
Section: Opll Susceptibility Genes and Signalingmentioning
confidence: 99%
“…Three different SNPs of COL6A1 have been found to be associated with OPLL: promoter (-572T), intron 32(-29) and intron 33 (+20) [ 20 , 35 - 37 ]. Wei et al have found two SNPs of COL17A1 , rs805698 (c.G1282A, p.G428S) and rs4918079 (c.C2595T, p.R865R), are significantly associated with OPLL via a whole exome sequencing [ 38 ]. The specific roles of these SNPs of collagen genes in the pathogenesis of OPLL remain unclear, though their contributions to the formation of extracellular matrix scaffolds may facilitate endochondral ossification.…”
Section: Opll Susceptibility Genes and Signalingmentioning
confidence: 99%
“…The pathogenesis of OPLL remains unclear, and genetic factors are considered to play a predominant role in the development of cervical OPLL (C-OPLL) (11,12). To date, more than 10 susceptibility genes/loci have been shown to be associated with susceptibility to C-OPLL (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, few studies have assessed the contribution of T-OPLL susceptibility genes.…”
Section: Introductionmentioning
confidence: 99%